PREVALENCE OF DENTAL HYPERSENSITIVITY IN PATIENTS WITH GINGIVAL RECESSION - Cava-Vergiú, Carlos (2016)
Objective: The presence of gingival recession, and the relationship with dental hypersensitivity was evaluated. Material and methods: an investigation was carried out in 300 patients who came to the Specialized Dentistry Clinic from the University San Martin de Porres, during the months of March to June of 2011. The sample was conformed by 166 teeth (from 51 patients) that had gingival recession. Most patients who experienced gingival recession (66%) were women. Results: From the 300 patients examined, only 51 (17%) presented some type of gingival recession not associated with periodontal disease. An increased frequency of gingival recession was found in patients with ages between 35 and 50 years, also 58 teeth (equivalent to the 35% of them 166 teeth evaluated) presented some type of sensitivity (to the air or to the touch). Conclusions: The present research showed that there is a direct relationship between patients with gingival recession (not associated with periodontitis) and the